Teacher Strategy in Developing Students' Good Morals Through Habits at SDI Nurul Qur'an - Maungi Dhotul Khasanah; Arfina Mei Damalia; Agus Purwowidodo; Muh. Nurul Huda (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This research aims to describe the teacher's strategy in fostering students' noble morals through habituation activities at SDI Nurul Qur'an. This study uses a descriptive qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation to obtain an in-depth picture of the forms of habituation applied and the role of teachers in guiding and being a role model for students. Data were analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the habituation strategy is carried out consistently through daily activities such as morning greetings, dhuha prayers, tahfidz, and congregational prayers. Teachers do not only act as teachers, but also become real examples in attitudes and behavior. Through ongoing habituation, students become accustomed to being polite, friendly, obedient to teachers, and demonstrating behavior that reflects noble morals. This strategy also supports student achievement in various aspects. With this approach, the formation of character and noble morals can grow naturally in a conducive and religious environment.